Digital Skills Competencies Required by Electrical Engineering Lecturers for Effective Utilization of Open Educational Resources in Polytechnics in Northeast Nigeria - Fwah, Karnilius Gideon; Ibanga, Isaac John; Philip, Sunday (ALSYSTECH Journal of Education Technology, 2024)
The study determined the digital skills competencies required by Electrical Engineering Lecturers for effective utilization of Open Educational Resources in Polytechnics in Northeast Nigeria. Four research questions guided the study which survey research design was adopted. The study population comprised 186 individuals, consisting of 151 Electrical/Electronic Engineering Technology Lecturers and 35 ICT unit heads from across 12 Polytechnics in North East Nigeria. Due to the manageable size of the population, no sampling was conducted; instead, the entire population was included in the study. Data collected for the study was through a structured questionnaire developed by the researchers, termed the “Open Educational Resources Digital Skills Competencies Questionnaire (OERDSCQ)”, employing a 5-point Likert and Rating scales. The questionnaire underwent validation by three experts and a trial test was conducted on five lecturers and four ICT unit staff at Yobe State Polytechnic, Damaturu, where a reliability index of 0.89 was achieved using the Cronbach Alpha method. The mean statistic was utilized to answer the four research questions. Based on the results, the study revealed that across eleven clusters of competencies ranging from technical skills to pedagogical competencies, all competencies were deemed necessary for effective teaching and learning in electrical engineering technology; and regarding the accessibility of open educational resources (OERs) in Northeast Nigerian Polytechnics reveal a significant discrepancy in availability and ease of access to OER. The study recommended that the government should implement structured digital skills training programs tailored to the needs of electrical engineering lecturers in Northeast Nigerian Polytechnics; and the government should invest in infrastructure and technological resources to enhance access to digital tools and resources within Northeast Nigerian Polytechnics.